Deoxyribozyme Cascade for Visual Detection of Bacterial RNA. Issue 16 (17th September 2013) - Gerasimova, Yulia V.; Cornett, Evan M.; Edwards, Emily; Su, Xiaoli; Rohde, Kyle H.; Kolpashchikov, Dmitry M.
<x xml:space="preserve">Abstract</x> In the blink of the eye: A cascade of two deoxyribozymes was designed for rapid visual detection of bacterial 16S rRNA. The detection limit is 12.5 ng by the naked eye, with the ability to differentiate between closely related pathogenic and nonpathogenic species.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>